Evaluating the impact of natural fertilizers on growth dynamics and yield performance of Solanum melongena L. - Warghane, Ashish; Thakkar, Jigisha; Chauhan, Kartik; Zala, Dolatsinh; Patel, Harsh; Bhatt, Vaibhav; Chopade, B. A. (Frontiers in Sustainable Food Systems, 2025)
A one-year field experiment (2023–2024) was laid out in a randomized complete block design (RCBD) with a spacing of 50 × 40 cm involving three replications with five treatments having cow manure along with integrated nutrient management in a plot size of 4.0 m × 1.5 m. The effect of cow manure and mineral fertilizers on soil fertility, nutrient uptake, yield, and farmers’ economic profitability. The experiment was laid out during the Rabi season of the Ahmedabad region. T2 (250 mL of Jivamrit) and T3 (500 mL of Jivamrit) obtained high brinjal production compared to other crops. Also, these two treatment plants contain high organic carbon content, available N, P, K in the soil and more N, P and K uptake by the plants. Further, this treatment obtained the greatest value for yield and net income. The outcomes of this investigation suggested that the combined usage of cow manure prepared Jivamrit with the proper dose gave the best result in the crop and a high crop yield. The present study reveals that Jivamrit would be used as a natural fertilizer for sustainable farming, which minimizes the hazardous effect of chemical fertilizers.